Severe cutaneous adverse drug reactions - Chung, Wen-Hung; Wang, Chuang-Wei; Dao, Ro-Lan (Journal of dermatology, 2016)
The clinical manifestations of drug eruptions can range from mild maculopapular exanthema to severe cutaneous adverse drug reactions (SCAR), including drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms, Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) which are rare but occasionally fatal. Some pathogens may induce skin reactions mimicking SCAR. There are several models to explain the interaction of human leukocyte antigen (HLA), drug and T‐cell receptor (TCR): (i) the “hapten/prohapten” theory; (ii) the “p‐i concept”; (iii) the “altered peptide repertoire”; and (iv) the “altered TCR repertoire”. The checkpoints of molecular mechanisms of SCAR include specific drug antigens interacting with the specific HLA loci (e.g. HLA‐B*15:02 for carbamazepine‐induced SJS/TEN and HLA‐B*58:01 for allopurinol‐induced SCAR), involvement of specific TCR, induction of T‐cell‐mediated responses (e.g. granulysin, Fas ligand, perforin/granzyme B and T‐helper 1/2‐associated cytokines) and cell death mechanism (e.g. miR‐18a‐5p‐induced apoptosis; annexin A1 and formyl peptide receptor 1‐induced necroptosis in keratinocytes). In addition to immune mechanism, metabolism has been found to play a role in the pathogenesis of SCAR, such as recent findings of strong association of CYP2C9*3 with phenytoin‐induced SCAR and impaired renal function with allopurinol SCAR. With a better understanding of the mechanisms, effective therapeutics and prevention for SCAR can be improved.